(untitled) (American Journal of Islam and Society, 2007)
On 5 June 2007, the fortieth anniversary of the Six Day War and the Israeli occupation of Palestine, the Kay Spiritual Life Center hosted “Forty Years after the War of June 1967: Is Israeli-Palestinian Peace Possible?” on the campus of American University in Washington, DC. This panel featured Yuval Rabin (son of former Prime Minister Yitzhak Rabin; governing board, the Rabin Center), Amjad Atallah (president, Strategic Assessments Initiative), Aaron David Miller (public policy scholar, the Woodrow Wilson Center), and Ziad Asali (president, American Task Force on Palestine; panel chair). Rabin opened by describing the Six Day War as “a war of our existence.” He discussed the importance of the Camp David, Oslo, and other negotiations and then talked about Israel’s 1967 victory. After stating that both sides in this continued conflict have faced hardship, he also mentioned the lack of knowledge involving certain issues. Atallah explained how Americans are bogged down with this conflict’s technicalities, such as the number of checkpoints, which causes them to neglect the bigger picture. He pointed out that on 29 November 1947, the United Nations General Assembly passed a resolution (33 to 13) recommending that Palestine be partitioned into two states, with over half of the land going to the Jews and the rest going to the Palestinians. By May 1948, according to the United Nations and the State Department, 350,000 Palestinians had been expelled from their homes. The Arab states declared war on Israel and, outnumbered and under-equipped, 400,000 more Palestinians were expelled. At the time, the Israelis accepted partition and the Arabs rejected the plan. He explained that the Israelis rushed to the Sinai Peninsula and the Jordan river and fully understood the rules of diplomacy. This resulted in Jordan taking over what is now the West Bank. In the course of the Six Day War, another 600,000 Palestinians were displaced, some for the second time ...